Endovascular treatment for chronic lower extremity ischaemia with sub-acute deterioration. (July 2017) - Yuan, Liangxi; Guo, Songlin; Dong, Jian; Zhou, Jian; Lu, Qingsheng; Bao, Junmin; Jing, Zaiping
Objectives: The purpose of this study is to report the efficacy of endovascular treatment for patients with sub-acute (14-day to 2-month) deterioration of chronic lower extremity ischaemia. Materials and Methods: Between June 2013 and May 2015, 26 consecutive patients (22 men, 4 women; mean age, 68.6 years; range, 50–86 years) were treated for sub-acute deterioration of chronic lower extremity ischaemia in our hospital. All patients were treated with catheter-directed thrombolysis initially and then adjunctive percutaneous transluminal angioplasty and/or stenting was performed to correct underlying lesions. Results: The 26 intra-arterial thrombolysis procedures were all performed in native lower arteries including 8 iliac, 13 femoropopliteal and 5 diffuse occlusions involving the iliac and femoropopliteal segments. Lesion length decreased from 194 mm (70–350 mm) to 92 mm (20–270 mm) after the thrombolytic procedures, and the residual lesions were corrected with percutaneous transluminal angioplasty alone in 4 (15.4%) limbs and stenting in 22 (84.6%) patients. No cross-joint stenting was seen in the 22 affected limbs that used stents. Throughout the treatment process, nine patients with intermittent claudication achieved an unrestricted walking distance, and 17 patients with rest pain or foot ulcers showed significant symptom improvement. The mean ankle-brachial index increased from 0.42 ± 0.16 preoperatively to 0.81 ± 0.25 postoperatively ( p < 0.01). Conclusion: Endovascular therapy with catheter-directed thrombolysis and percutaneous transluminal angioplasty/stenting is feasible for sub-acute deterioration of chronic lower extremity ischaemia patients with favourable midterm results.